If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+13x-4=5(4x-4)
We simplify the equation to the form, which is simple to understand
7x+13x-4=5(4x-4)
Reorder the terms in parentheses
7x+13x-4=+(+20x-20)
Remove unnecessary parentheses
+7x+13x-4=+20x-20
We move all terms containing x to the left and all other terms to the right.
+7x+13x-20x=-20+4
We simplify left and right side of the equation.
0x=-16
0=-16
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 9b+9b=72 | | -0.7+0.5+12x=0.5x+0.8 | | -1.2x+11+2.6x= | | 9x+4=86 | | 9X+3=3X | | 218=119-x | | 7.30=4x+6 | | 4r+3=10 | | 1.3x-5.4x-5.4x+3= | | 35-3x=10+6x | | 1.3h-4(2.3h-3)=2.3h-6 | | 5x+7y=300solvey | | 2(5z+2)-3(z+1)= | | -11r-3+12r+2= | | 0=2x^2-3x-104 | | x+x+3=31 | | 12x=10+2 | | z=(x-4)k | | 8r^3+24r^2=32r | | 2.2n+4-9-4.5n= | | 6y(6-x)= | | -4m+14=-2m-10 | | 5/6+6/12-22-2= | | 180=x^3+x^2 | | (9+j)+6=jwhatisJ | | 7u=2u+15 | | 145+36=433 | | 2(x+3y)-4(2x-8y)= | | 2(x-3)+5=3(z-1) | | Z(2z-9)(z+3)=0 | | 0.6(x+20)+08(x-10)=46 | | 5x-2(x+3)=40 |